PENGUATAN PENDIDIKAN KARAKTER (PPK) BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) - Subadar Subadar (Nurul Jadid University, 2017)
Nowadays, Some phenomena indicate an increasing in juvenile delinquency cases, both in terms of quantity and quality. it can be used as one of the declining factors of ethics, morals and character of the nation. This phenomenon, of course, can not be separated from the role of education, especially education in schools. In accordance with these issues, the government is currently promoting the strengthening of character education to minimize the existing problems. These issues also form the basis of the curriculum revision. The current 2013 curriculum is the government's effort to improve the existing education system by validating standardt in content and assessment. The government's expectations of this curriculum change can force learners to improve their ability to think creatively and think in high-level. High order thinking skills is to prepare the generation to face increasingly complex global challenges. High order thinking can be done by training students through contextual and meaningful classroom learning. Thematic learning is theme based learning, so as to create a contextual and meaningful learning for learners.